PERSEPSI MASYARAKAT GAMPONG TANAH BARA KECAMATAN GUNUNG MERIAH KABUPATEN ACEH SINGKIL TERHADAP ZAKAT HASIL SAWIT - Khairuddin Khairuddin (SYARIAH: Journal of Islamic Law, 2020)
Many people in Aceh are involved in oil palm plantations, including in Aceh Singkil, moreover, prices are stable, so it's no wonder that every community dreams of having oil palm plantations, oil palm products that generate a lot of money are a problem whether it is a type of zakat or not. The main problems in this research are (1) how is the review of Islamic law on the zakat law for oil palm? (2) what is the community's perception regarding the zakat law from oil palm plantations? The purpose of this study is to determine the law of oil palm zakat in the perspective of Islamic law and the perceptions of the Tanah Bara village community. The type of research the writer will use is descriptive method research with a qualitative approach. The data collection techniques by means of observation, interviews and documentation. The results of this study indicate that the community's understanding of the zakat law from oil palm business is different, some people do not think that oil palm is a type of asset that must be zakat and others think that palm oil is a type of asset that must be paid zakat when it reaches the nisab of 653 kg or the value of zakat. Gold, namely 85 grams of gold in one year is issued 2.5% of zakat and is given to teachers of the Koran, relatives in the meaning of the word not according to the targets described in the Koran.